2012
DOI: 10.1371/journal.pone.0030648
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Spore-Like Morphotype in Chronically Starved Mycobacterium avium Subsp. Paratuberculosis Cultures

Abstract: Mycobacteria are able to enter into a state of non-replication or dormancy, which may result in their chronic persistence in soil, aquatic environments, and permissive hosts. Stresses such as nutrient deprivation and hypoxia provide environmental cues to enter a persistent state; however, a clear definition of the mechanism that mycobacteria employ to achieve this remains elusive. While the concept of sporulation in mycobacteria is not novel, it continues to spark controversy and challenges our perceptions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(67 citation statements)
references
References 58 publications
0
65
1
1
Order By: Relevance
“…through irrigation) and seafood. Further research is required to examine how hardy M. paratuberculosis is in its spore-like state and how long it survives in manure storage and composting to better understand the risk of contaminating other potential environmental sources of M. paratuberculosis for humans (Lamont et al, 2012 (Singh et al, 2013;Ahlstrom et al, 2015). The multitude of molecular methods used to date has been a barrier to meaningful synthesis of molecular epidemiological results (Ahlstrom, et al, 2015;Muellner, et al, 2015), therefore as data from whole genome sequencing become more widely used in epidemiological investigations, researchers should seek consensus on target markers to aid in the comparability of results across studies.…”
Section: Discussionmentioning
confidence: 99%
“…through irrigation) and seafood. Further research is required to examine how hardy M. paratuberculosis is in its spore-like state and how long it survives in manure storage and composting to better understand the risk of contaminating other potential environmental sources of M. paratuberculosis for humans (Lamont et al, 2012 (Singh et al, 2013;Ahlstrom et al, 2015). The multitude of molecular methods used to date has been a barrier to meaningful synthesis of molecular epidemiological results (Ahlstrom, et al, 2015;Muellner, et al, 2015), therefore as data from whole genome sequencing become more widely used in epidemiological investigations, researchers should seek consensus on target markers to aid in the comparability of results across studies.…”
Section: Discussionmentioning
confidence: 99%
“…Still, MAP isolation in milk sampled at retail stores has been reported (Ellingson et al, 2005;Stephan et al, 2007). It has recently been reported that spore-forming MAP may survive heat treatments of 70°C (Lamont et al, 2012), which could explain the occasional MAP survival after heat treatments. Other possible explanations for the difference between our predictions and the apparent pasteurization inefficiency include the following: (1) inappropriate pasteurization was conducted for the retail store samples; (2) the maximum amount of feces per cow is much higher than the 10 g/cow we used; or (3) the maximum amount of MAP per gram of feces is much higher than that included in our model.…”
Section: Discussionmentioning
confidence: 99%
“…The bacteria inside the clumps would be protected from the heat by those on the outer surface during pasteurization [13,24]. In addition to the formation of clumps, MAP also has the ability to form a spore-like structure that may hinder its elimination and favor bacterial survival in the environment, as observed in aquatic environments, since MAP has been identified in raw milk and untreated water [11,13,26,27].…”
Section: Moreira Mas Austin Publishing Groupmentioning
confidence: 99%
“…Infected patients may develop intestinal problems associated with a genetic propensity, including mutations in the Nod 2, which is gene associated with the processing of modified bacterial products [9,27]. Besides, individuals infected with the agent may contaminate their families through direct contact or fomites of contamination.…”
Section: Moreira Mas Austin Publishing Groupmentioning
confidence: 99%